Physical-mechanical evaluation of asphalt mixtures through the addition of recycled motor oil - Raffo Suclupe, Carlos Lucio (2023)
This study was developed by an experimental design of a hot mix asphalt (HMA), seeking to mitigate the negative impact on the environment that generate the recycled motor oils (RMO) or commonly known as burned oil which, in general, is eliminated outdoors. Then, RMO was added in percentages to an asphalt mixture in different percentages according to the PEN 60/70 of the standard mixture, with the objective of determining the resulting physical-mechanical properties of the modified asphalt mixture and evaluating if they meet the standards. A total population of 135 briquettes of modified mixtures was evaluated by means of the Marshall methodology. The mixtures contained 0,5 %, 1,5 %, 2,5 % and 3,5 % of recycled oil. It was found that the optimal percentage of asphalt is 5,75 %, rehearsed at temperatures of 120 °C and 130 °C. It is concluded that after incorporating RMO in the asphalt mixture, its physical-mechanical properties (rigidity, flow, stability) were improved and comply with the minimum parameters of an HMA stated by standards.